Investigation on the local electronic/atomic structure properties using XANES/EXAFS and photocatalyst application of Zr1-xCuxO2 (0 <= x <= 0.2) - Sharma, Aditya; Varshney, Mayora; Chae, Keun Hwa; Shin, Hyun Joon; Won, Sung Ok (ELSEVIER SCIENCE BV, 2016)
We investigated local electronic/atomic structure properties by using X-ray absorption spectroscopy and demonstrated the photocatalyst application of Zr1-xCuxO2 (0 <= x <= 0.2) samples. X ray diffraction (XRD) results revealed the amorphous nature of the samples; however, transmission electron microscopy (TEM) depicted the formation of < 2 nm sized particles in all of the samples. Local electronic structure was investigated by X-ray absorption near edge structure (XANES) at O K-edge, Zr K-edge and Cu K-edge. The O K-edge XANES suggested strong hybridization of s-p-d orbitals upon Cu doping. The Cu K-edge XANES confirmed +1 valence state of Cu (Cu+1) in all of the Cu doped ZrO2 samples. Extended X-ray absorption fine structure (EXAFS) analysis at the Zr K-edge nullifies the formation of trivial phases and confirms the local monoclinic structure in all of the samples. Photocatalyst properties of the samples were investigated by monitoring the net degradation in the methyl orange dye aqueous solution under the UV light irradiation. The Cu doped ZrO2 samples exhibited superior photo-catalyst properties over the undoped ZrO2. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: RAY-ABSORPTION SPECTROSCOPY; NANOPARTICLES; OXIDE; NANOSTRUCTURES; ZRO2; CATALYSTS; XANES; XAFS